Bibliotherapy Sebagai Upaya Meningkatkan Keterampilan Interpersonal Remaja - Triana Rosalina Noor (Jurnal Studia Insania, 2020)
Literature or books is one of media that used to obtain information, knowledge and self-development. In addition literature also can be used to improve self development, especially teenagers. It becaused some teenagers has not optimize on improving  their selves. They still have lack of interpersonal skills that make them difficult to do good  adaption in their social environment. Bibliotherapy or or reading therapy is one alternative in dealing with self-development problems. In this way teenagers are expected to develop a more positive sense of themselves, provide insights into a problem, stimulate discussion of problems, provide solutions to problems, communicate new values and attitudes, and discover meaning in life. The choosen process of literature literature based on what problem  faced. The goal is the process of reading therapy  in order improving  teenagers interpersonal skills maximized. In addition, the application of bibliotherapy also consider the interests and learning styles that are owned by teenagers.Bibliotherapy is very effective therapy  for improving understanding and adding insight into teenagers  according to reading material. Through bibliotherapy, teenagers  are expected to find insight over obstacles their selves develompment to improve better interpersonal skills.